Commercial DNA extraction kits impact observed microbial community composition in permafrost samples. Issue 1 (17th October 2013) - Vishnivetskaya, Tatiana A.; Layton, Alice C.; Lau, Maggie C. Y.; Chauhan, Archana; Cheng, Karen R.; Meyers, Arthur J.; Murphy, Jasity R.; Rogers, Alexandra W.; Saarunya, Geetha S.; Williams, Daniel E.; Pfiffner, Susan M.; Biggerstaff, John P.; et al.
Abstract The total community genomic DNA (gDNA) from permafrost was extracted using four commercial DNA extraction kits. The gDNAs were compared using quantitative real‐time PCR (qPCR) targeting 16S rRNA genes and bacterial diversity analyses obtained via 454 pyrosequencing of the 16S rRNA (V3 region) amplified in single or nested PCR. The FastDNA® SPIN (FDS) Kit provided the highest gDNA yields and 16S rRNA gene concentrations, followed by MoBio PowerSoil® (PS) and MoBio PowerLyzer™ (PL) kits. The lowest gDNA yields and 16S rRNA gene concentrations were from the Meta‐G‐Nome™ (MGN) DNA Isolation Kit. Bacterial phyla identified in all DNA extracts were similar to that found in other soils and were dominated by Actinobacteria, Firmicutes, Gemmatimonadetes, Proteobacteria, and Acidobacteria. Weighted UniFrac and statistical analyses indicated that bacterial community compositions derived from FDS, PS, and PL extracts were similar to each other. However, the bacterial community structure from the MGN extracts differed from other kits exhibiting higher proportions of easily lysed β‐ and γ‐Proteobacteria and lower proportions of Actinobacteria and Methylocystaceae important in carbon cycling. These results indicate that gDNA yields differ between the extraction kits, but reproducible bacterial community structure analysis may be accomplished using gDNAs from the three bead‐beating lysis extraction kits.